Stanley Fish on philosophy, politics and law : how Fish works - Robertson, Michael Spencer, 1952- (Cambridge, United Kingdom : Cambridge University Press, 2014)
"Fish's writings on philosophy, politics and law comprise numerous b ooks and articles produced over many decades. This book connects those dots in order to reveal the overall structure of his argument and to de monstrate how his work in politics and law flows logically from his phi losophical stands on the nature of the self, epistemology and the role of theory. Michael Robertson considers Fish's political critiques of li beralism, critical theory, postmodernism and pragmatism before turning to his observations on political substance and political practice. The detailed analysis of Fish's jurisprudence explores his relationships to legal positivism, legal formalism, legal realism and critical legal st udies, as well as his debate with Ronald Dworkin. Gaps and inconsistenc ies in Fish's arguments are fully explored, and the author provides a d escription of Fish's own positive account of law and deals with the cha rge that Fish is an indeterminacy theorist who undermines the rule of l aw"--
Machine generated contents note: Introduction; Part I. Philosophy: 1 . The nature of the self; 2. Epistemology; 3. The role of theory; Part II. Politics: 4. Political theory; 5. Political substance; 6. Political practice; Part III. Law: 7. Legal positivism; 8. Legal formalism; 9. T he Fish/Dworkin debate; 10. Fish's positive account of law; 11. Change and indeterminacy in law; 12. Legal realism and critical legal studies; Conclusion.
Includes bibliographical references and index.
Keywords: Fish, Stanley Eugene; Law -- Philosophy; Political science -- Philosophy